Hybrid reconstruction of distal nasal defects - YILDIZ, KEMALETTİN; YILDIZ, KEMALETTİN; Gorgulu, Tahsin; Yesiloglu, Nebil; Kelahmetoglu, Osman; ÇAMLI, MEHMET FATİH; ÇAMLI, MEHMET FATİH; Canter, Halil Ibrahim (My University, 2021)
We present hybrid reconstruction of distal lateral -through-and-through- nasal defects (skin, cartilage, and mucosa) due to resection of tumor and/or infection. Retrospective descriptive study. The study was performed in multicenter clinics between July 2011 and September 2016. 13 patients with full thickness distal nasal defects secondary to tumor and/or infection were included. Defects included dorsal and/or caudal septum, upper lateral cartilage, or inner/outer nasal valve. Caudal-based turn-in flaps were planned and used to repair inner lining of nasal cavity. Conchal and septal cartilages were used as cartilage grafts. Skin defects were reconstructed with lateral nasal artery perforator flaps. All flaps healed uneventfully, without flap loss. Nasal passage collapse, adhesion, or difficulty in breathing were not seen. No hematoma, infection, and deformity at cartilage graft donor areas was observed. During nasal reconstruction, it is mandatory to consider 3D complex and functional structure of nose. The repair of skin defects may not be enough for functional restoration. We believe that single step reconstruction of full thickness nasal defects through hybrid reconstruction may lead to anticipated successful results.